Differential Effects of VR and Early Clinical Exposure on Undergraduate Competency in Dental Trauma Management: A Randomized Crossover Pilot Study - Ningxin Zhu; Xijun Jiang; Jing Li (Journal of Dental Education, 2026)
ABSTRACT Objective This study evaluated the effectiveness of a virtual reality (VR)‐based dental training system in enhancing clinical decision‐making and operational skills among undergraduates managing complicated coronal fractures in young permanent teeth, a foundational competency in dental traumatology. Methods Sixty dental undergraduates were randomly divided into a VR training‐first group ( n = 30) and a conventional instruction‐first group ( n = 30). A crossover design was implemented with assessments at baseline (T1), after the first intervention (T2), and after the crossover phase (T3, wherein the two groups swapped instructional modalities). All participants received standard pre‐clinical training before the pediatric dentistry rotation. The conventional instruction‐first group directly began patient management under supervision, while the VR training‐first group underwent a 2‐week specialized training module for young permanent tooth coronal fractures (two 40‐min sessions per week). Effects were evaluated using the VR system's assessment module, clinical performance scores, a self‐rated diagnostic confidence scale, and a teaching satisfaction survey. Results Following the initial intervention phase (T2), distinct timing effects were observed. The VR training‐first group demonstrated an immediate technical advantage, achieving significantly higher proficiency in simulated pulp chamber access time, clinical procedural fluency, and hard tissue preservation during actual patient management compared to the conventional group ( p < 0.001). Conversely, the conventional instruction‐first group achieved significantly higher scores in pulp status assessment at T2 ( p = 0.005), reflecting the advantage of early direct clinical exposure for subjective diagnostic judgment. Following the crossover (T3), both groups attained comparable levels of overall clinical competency ( p > 0.05), confirming that intervention sequencing primarily dictates the chronological rate of specific competency acquisition rather than final clinical proficiency. Secondary survey data supported VR's psychological scaffolding effect in mitigating initial clinical anxiety. Conclusion This pilot study demonstrates that VR simulation significantly enhances undergraduate students’ objective procedural competency in managing complicated coronal fractures. Given that the acquired skills, particularly precise hard tissue preservation, are universally applicable to broader dental trauma and general endodontics, VR serves as a highly effective complementary adjunct to safely bridge the gap between theoretical knowledge and patient‐based clinical learning.